Alternative pressurized liquid extraction using a hard cap espresso machine for determination of polycyclic aromatic hydrocarbons in smoked bacon. (February 2021) - Merlo, Thais Cardoso; Molognoni, Luciano; Hoff, Rodrigo Barcellos; Daguer, Heitor; Patinho, Iliani; Contreras-Castillo, Carmen J.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are noxious compounds that can be found in some foods, especially those submitted to the traditional smoking process. In this study, a novel pressurized liquid extraction based on hard cap espresso machine followed by liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) was developed to determine PAHs in smoked bacon. Method performance was evaluated in accordance to the Commission Decision 2002/657/EC in terms of selectivity, linearity, sensitivity, matrix effect, recovery and detection capability (CCβ ). Linearity was satisfactory with regression coefficients (R 2 ) higher than 0.98. Recoveries ranged from 73.9 to 99.9%. CCβ values ranged from 0.30 to 0.90 μg kg −1, values below the maximum limits suggested by Commission Regulation 835/2011, which propose 2.0 μg kg −1 for benzo [ a ]pyrene and 12.0 μg kg −1 for sum of the four priority PAHs. The method was applied to real samples, with PAHs levels below these limits. The developed method proved to be a fast and cheap approach for the efficient and reliable determination of PAHs in smoked bacon. Highlights: Four priority PAHs was determined in smoked bacon. Sample preparation and chromatographic approach were assessed. Hard cap espresso machine, a cheap and fast tool to extract PAHs from smoked bacon. Low levels of PAHs in smoked bacon were obtained.